Katekese Digital: Peran Pembina Dalam Membangun Minat Anak Untuk Terlibat Dalam Kegiatan Bina Iman (Jurnal Pendidikan Agama dan Teologi, 2024)
Church teaches all baptized Christians to take part in carrying out her duties as priest, prophet and king. A faith formation counselor by the power of the Holy Spirit is called to proclaim the good news to children. The good news is Christ himself. The coach must be able to encourage, motivate children and create an atmosphere where children are moved to grow and develop in living out their faith. The purpThe ose of this research is to find out the creativity of a coach, especially to make the process of faith formation activities interesting by using digital media. Because by using digital media children are more interested, excited and easier to understand the teaching of faith.